Neuroanesthesia Guidelines for Optimizing Transcranial Motor Evoked Potential Neuromonitoring During Deformity and Complex Spinal Surgery: A Delphi Consensus Study. Issue 13 (1st July 2020) - Walker, Corey T.; Kim, Han Jo; Park, Paul; Lenke, Lawrence G.; Weller, Mark A.; Smith, Justin S.; Nemergut, Edward C.; Sciubba, Daniel M.; Wang, Michael Y.; Shaffrey, Christopher; Deviren, Vedat; Mummaneni, Praveen V.; et al.
Abstract : Study Design: Expert opinion—modified Delphi study. Objective: We used a modified Delphi approach to obtain consensus among leading spinal deformity surgeons and their neuroanesthesiology teams regarding optimal practices for obtaining reliable motor evoked potential (MEP) signals. Summary of Background Data: Intraoperative neurophysiological monitoring of transcranial MEPs provides the best method for assessing spinal cord integrity during complex spinal surgeries. MEPs are affected by pharmacological and physiological parameters. It is the responsibility of the spine surgeon and neuroanesthesia team to understand how they can best maintain high-quality MEP signals throughout surgery. Nevertheless, varying approaches to neuroanesthesia are seen in clinical practice. Methods: We identified 19 international expert spinal deformity treatment teams. A modified Delphi process with two rounds of surveying was performed. Greater than 50% agreement on the final statements was considered "agreement"; >75% agreement was considered "consensus." Results: Anesthesia regimens and protocols were obtained from the expert centers. There was a large amount of variability among centers. Two rounds of consensus surveying were performed, and all centers participated in both rounds of surveying. Consensus was obtained for 12 of 15 statements, and majority agreement was obtained for two of the remaining statements. Total intravenous anesthesia was identified as the preferred method of maintenance, with few centers allowing for low mean alveolar concentration of inhaled anesthetic. Most centers advocated for <150 μg/kg/min of propofol with titration to the lowest dose that maintains appropriate anesthesia depth based on awareness monitoring. Use of adjuvant intravenous anesthetics, including ketamine, low-dose dexmedetomidine, and lidocaine, may help to reduce propofol requirements without negatively effecting MEP signals. Conclusion: Spine surgeons and neuroanesthesia teams should be familiar with methods for optimizing MEPs during deformity and complex spinal cases. Although variability in practices exists, there is consensus among international spinal deformity treatment centers regarding best practices. Level of Evidence: 5 Abstract : Using a modified Delphi approach, consensus was obtained among international deformity expert teams regarding the neuroanesthetic practices for high-fidelity motor evoked potential monitoring. Consensus statements surrounding anesthetic principles were derived and may help guide surgical teams that perform complex spinal procedures to obtain optimal MEP signals for their patients.